Human Resource Needs Assessment in the Health Sector Using Workload Analysis Method: A Literature Case Study - Firasghani, Muhammad Almy; Rinawati, Rinawati (Asosiasi Ahli Administrasi Indonesia, 2025)
Human resource planning is a critical element of healthcare systems, as adequate staffing directly influences service delivery and patient outcomes. The research design employed in this study is a comprehensive literature review that focuses on assessing human resource needs in the health sector through the lens of workload analysis methodologies, particularly the Health Workload Analysis Method (ABK-Kes) and the Workload Indicators of Staffing Need (WISN). Evidence from recent studies demonstrates that workload-based approaches provide more accurate estimations of staffing requirements compared to conventional methods, thereby improving operational efficiency, enhancing service quality, and supporting strategic workforce planning. The integration of technology in human resource management further contributes to optimizing staff allocation and addressing workforce shortages. Overall, the findings underscore the importance of adopting robust analytical methods to strengthen evidence-based decision-making, promote sustainability, and provide actionable insights for policymakers and healthcare administrators in developing effective staffing strategies.